Surveying 80 Years of Psychodrama Research: A Scientometric Review - Lim, Mengyu; Carollo, Alessandro; Chen, S. H. Annabel; Esposito, Gianluca (Frontiers in Psychiatry, 2021)
Almost a century after Jacob Levy Moreno pioneered the group practice of psychodrama, research in this area has flourished to include different sub-fields of study and psychodramatic intervention for various psychological conditions. By making use of scientometric analysis, particularly document citation analysis and keyword analysis, this study maps out dominant research domains in psychodrama since its inception. From these findings, projections of future research trends and an evaluation of psychodrama research are discussed. Generally, there has been an increased adoption of technology to facilitate psychodrama practice, along with an increasing integration of psychodramatic principles with other psychotherapies. To improve research in this area, this paper recommends greater transparency in the reporting of materials, processes and data used in publications. Finally, we encourage embracing new technological methods such as neuroimaging to provide greater insight into mechanisms of change in psychodrama. The field of psychodrama remains full of potential and innovations to be developed.